Mitigating mode instabilities by controllable mode beating excitation with a photonic lantern - Lu, Yao; Jiang, Zongfu; Xiao, Hu; Chen, Zilun; Jiang, Man; Chai, Junyu; Yang, Hao; Ding, Lianchuang; Zhang, Dan; Zhang, Jiangbin; Zhou, Qiong; Liu, Wenguang (Frontiers in Physics, 2023)
We demonstrate a method of stabilizing the output beam of a large mode area fiber amplifier operating above the mode instability threshold. A mode control system based on the photonic lantern is used to excite dynamic mode beatings as the seeding stage of a 42/250 µm Yb-doped fiber amplifier. We propose a theoretical explanation for the validity of this method: provided that the mode interference patterns generated by input mode beatings are antisymmetric to those in the main amplifier caused by thermally-induced nonlinear effect, the refractive index grating will not be formed to indicate the onset of mode instability. Experimentally, a significant mode stability and beam quality improvement has been achieved in this system at power levels of up to nearly four times the mode instabilities threshold.